Study of corrosion resistance of anodized aluminium 6063 - Paucar Cuba, Karín (2012)
The study of the corrosion resistance of anodized on aluminum alloy (AA6063) in sulfuric acid to different times: 30, 45 and 60 min. was performed using electrochemical impedance spectroscopy (EIS) and the acid salt spray test (ASTM B287). The EIS’data and its correlation with the most appropriate equivalent circuits allowed to determine the parameters associated with the porous layer and the oxide layer protective barrier formed on the aluminum surface under study. Exposure of the samples anodized for a 250h salt spray acid allowed to observe changes in their mass. From the results obtained by EIS and the mass losses of the anodized samples was established that the anodized film of 45 minutes showed higher corrosion resistance compared to that obtained at 60 and 30 min, respectively.